1999
DOI: 10.1345/aph.17385
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Associated with Olanzapine

Abstract: Considering all factors related to causality, the likelihood that olanzapine was responsible for precipitating seizure activity in this patient was judged possible. Although premarketing studies have indicated that olanzapine may be associated with minimal seizure liability, this case serves as a reminder that postmarketing surveillance of newly released medications is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 5 publications
1
19
0
1
Order By: Relevance
“…Recently, Lee et al reported the case of a 31-year-old woman who experienced seizure activity when switched from haloperidol to olanzapine treatment (Lee et al 1999). Several risk factors were present in this patient, including preexisting seizure disorder and concurrent pharmacotherapy (Lee et al 1999). In connection with the anecdotal observation of seizures under olanzapine treatment, our findings make EEG monitoring seem advisable in patients taking higher doses of olanzapine and in those with risk factors.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Recently, Lee et al reported the case of a 31-year-old woman who experienced seizure activity when switched from haloperidol to olanzapine treatment (Lee et al 1999). Several risk factors were present in this patient, including preexisting seizure disorder and concurrent pharmacotherapy (Lee et al 1999). In connection with the anecdotal observation of seizures under olanzapine treatment, our findings make EEG monitoring seem advisable in patients taking higher doses of olanzapine and in those with risk factors.…”
Section: Resultsmentioning
confidence: 58%
“…However, risk factors important in clinical routine (concomitant medication, neurological disease) are often excluded from controlled studies. Recently, Lee et al reported the case of a 31-year-old woman who experienced seizure activity when switched from haloperidol to olanzapine treatment (Lee et al 1999). Several risk factors were present in this patient, including preexisting seizure disorder and concurrent pharmacotherapy (Lee et al 1999).…”
Section: Resultsmentioning
confidence: 91%
“…In other reports it is more difficult to establish the main precipitating factor because patients were receiving simultaneously olanzapine and other potentially proconvulsant drugs when seizures appeared. [8][9][10] There is one dramatic case that ended in fatal status epilepticus, 11 but in the remaining reports seizure activity could be controlled either by olanzapine discontinuation or by concurrent antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic administration of APs is known to alter the regional density of several neurotransmitter receptors in the central nervous system, including those for dopamine, serotonin, acetylcholine, histamine, and glutamate, that may contribute to the observed proconvulsant effects of some antipsychotics [42,53,54]. These changes, in particular upregulation of dopamine receptors, have been suggested as the basis for some of the adverse effects that occur with long-term antipsychotic therapy [55].…”
Section: General Considerations On the Effect Of Aps On Seizuresmentioning
confidence: 99%